The Role of Oxidative Stress Markers in Predicting Acute Thrombotic Occlusion of Haemodialysis Vascular Access and Progressive Stenotic Dysfunction Demanding Angioplasty - Jenq-Shyong Chan; Po-Jen Hsiao; Wen-Fang Chiang; Prabir Roy-Chaudhury (MDPI AG, 2021)
Haemodialysis vascular access (VA) dysfunction is a major cause of morbidity in haemodialysis (HD) patients. Primary venous outflow occlusion and restenosis after percutaneous transluminal angioplasty (PTA) are two major obstacles for the long-term use of dialysis VA. It remains unclear whether oxidative stress markers can be used as predictors for thrombotic occlusion of VA and progressive stenosis dysfunction demanding PTA. All routine HD patients at one teaching hospital participated in this study including ankle-brachial index (ABI) examinations and serum oxidative stress markers. The serum oxidative stress markers (high-sensitivity C-reactive protein (hs-CRP), matrix metalloproteinase-2 (MMP-2), MMP-9, homocysteine, asymmetrical dimethylarginine (ADMA), nitrate oxidase (NO), tumour necrosis factor-α (TNF-α), monocyte chemotactic protein 1 (MCP-1), interleukin-1β (IL-1β), and transforming growth factor-β (TGF-β)) were measured using immunosorbent assays in 159 HD patients (83 men and 76 women; mean age: 65 ± 12 years). The participants met the following criteria: (1) received regular HD treatment for at least 6 months, without clinical evidence of acute or chronic inflammation, recent myocardial infarction, unstable angina or circulatory congestion; and (2) received an arteriovenous fistula (AVF)/arteriovenous graft (AVG: polytetrafluoroethylene, PTFE) as the current VA for more than 6 months, without interventions within the last 6 months. All the participants were followed up clinically for up to 12 months to estimate the amount of primary thrombotic occlusion and VA dysfunction demanding PTA. During the 12-month observation, 24 patients (15.1%) had primary thrombotic occlusion of VAs. Another 24 patients (15.1%) required PTA because of clinical dysfunction of access. Additionally, during the follow-up period, restenosis occurred in 12 patients (50% of 24 patients). The access types of arteriovenous grafts (AVGs) and a diagnosis of peripheral arterial occlusive disease (PAOD) were two strong predictors for acute thrombotic events of VA (hazard ratio (HR): 16.93 vs. 2.35; p < 0.001 vs. 0.047). Comparing dysfunctional with non-dysfunctional VAs, up to 27.7% of patients with high levels of ADMA (>0.6207 μM, N = 65) received required PTA compared with 4.4% of those with low levels (≤0.6207 μM; N = 90; p < 0.001). In multivariate analysis, the plasma baseline levels of ADMA independently conferred nearly 4.55 times the risk of primary stenotic dysfunction of HD VA (HR: 4.55; 95% confidence interval: 1.20 to 17.26; p = 0.026). In conclusion, our findings suggest the role of ADMA in the development of symptomatic VA dysfunction. Additionally, PAOD severity can be used in clinical practice to predict whether acute thrombotic occlusion of VA will easily occur in HD patients.